2014
DOI: 10.1016/j.tube.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

ESX1-dependent fractalkine mediates chemotaxis and Mycobacterium tuberculosis infection in humans

Abstract: SummaryMycobacterium tuberculosis-induced cellular aggregation is essential for granuloma formation and may assist establishment and early spread of M. tuberculosis infection. The M. tuberculosis ESX1 mutant, which has a non-functional type VII secretion system, induced significantly less production of the host macrophage-derived chemokine fractalkine (CX3CL1). Upon infection of human macrophages ESX1-dependent fractalkine production mediated selective recruitment of CD11b+ monocytic cells and increased infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…CXC3CL1, lysophosphatidylcholine, sphingosine-1-phosphate, ATP, and UTP) that attract phagocytic cells for the clearance of apoptotic bodies [85]. Which of these or other possible signals operate in TB is presently conjectural but available data hint at a role for CX3CL1 and its receptor CX3CR1 [86]. While ATP/P2X7R interactions are implicated in TB defense [87], P2Y2 is the sensor for the small amounts of nucleotides released from apoptotic cells and so far this receptor has not been linked to TB.…”
Section: Cell Death In Tbmentioning
confidence: 99%
“…CXC3CL1, lysophosphatidylcholine, sphingosine-1-phosphate, ATP, and UTP) that attract phagocytic cells for the clearance of apoptotic bodies [85]. Which of these or other possible signals operate in TB is presently conjectural but available data hint at a role for CX3CL1 and its receptor CX3CR1 [86]. While ATP/P2X7R interactions are implicated in TB defense [87], P2Y2 is the sensor for the small amounts of nucleotides released from apoptotic cells and so far this receptor has not been linked to TB.…”
Section: Cell Death In Tbmentioning
confidence: 99%
“…Both Fractalkine and VEGF are expressed by endothelial cells to mediate lymphocyte chemoattraction and adhesion in mucosal tissues [ 43 ] and promote formation of new blood vessels [ 44 ], respectively. Although the role of these proteins during TB infection has not been established, previous studies in animal models suggested that Fractalkine could mediate cellular infection and spread of Mtb bacilli [ 45 ] and VEGF has been suggested as a mechanism for Mtb spreading [ 46 ]. All this suggests that endothelial cells have an influence on the markers detected in saliva, and could be indirectly related with Mtb spreading in active TB patients.…”
Section: Discussionmentioning
confidence: 99%
“…First discovered by Bazan et al in 1998 (67), fractalkine is a rather unusual chemokine and in a class of its own, having a strange stalk-like structure that can also tether host cells. It has been reported to attract naive macrophages to the lung, and fractalkine production from M. tuberculosis -infected cells has been determined to be ESX-1 regulated (68). This study also linked fractalkine levels to the influx of naive macrophages during TB infection using bronchoalveolar lavage samples taken directly from the lungs of TB patients.…”
Section: The Esx-1 Secretion System and Its Proteinaceous Armymentioning
confidence: 99%
“…This study also linked fractalkine levels to the influx of naive macrophages during TB infection using bronchoalveolar lavage samples taken directly from the lungs of TB patients. Other cytokines are likely involved in this influx, such as ESX-1-regulated IL-1R (66, 68, 69).…”
Section: The Esx-1 Secretion System and Its Proteinaceous Armymentioning
confidence: 99%
See 1 more Smart Citation